Mpa'a Gopa Game-Based Physical Education Learning Media to Improve the Kinesthetic Abilities of Special Needs Students - Fauqi, Amal; Ilham, Ilham; Imansyah, M. Nur; Kurniawan, Syafaruddin; Ferdiansyah, Ferdiansyah (Jurnal Porkes, 2025)
This study developed a valid, practical, and effective traditional Mpa'a Gopa game-based physical education learning medium to improve the kinesthetic abilities of students with special needs at SLBN 1 Dompu. The method used was Research and Development (R&D) with a 4-D model, involving 20 students as samples. The Define stage revealed that 50% of students were passive and that there were limitations in adaptive media through observation and interviews with teachers. The Design stage produced a prototype of Mpa'a Gopa with modified rules and visual guidelines. The Develop stage involved expert validation and practicality and effectiveness tests using teacher-student response questionnaires and kinesthetic tests. The expert validation results showed that the media was highly valid with a score of 87.01%. Practicality tests proved the media to be very practical, as shown by positive responses from teachers (91.33%) and students (88%). Meanwhile, effectiveness tests showed a significant increase in kinesthetic abilities of 26.15% (from an average score of 65 to 82), exceeding the target of 20%. These findings indicate that Mpa'a Gopa is capable of encouraging active participation and developing gross motor skills. This media is innovative, contextual, and provides a solution to the monotony of PJOK learning in SLB.